Properties Enhancement Effect Of The Electrosprayed Carbon Nanotube Coating On Glass Fibre Epoxy Laminated - Khairuddin, Nur Aishahatul Syafiqa Mohammad (2019)
In this study, the fillers carbon nanotubes has been added into the glass fibre/epoxy laminated composite by using the electrospraying techniques and had significantly improved the composite properties. Mechanical properties obtained for nanocomposite laminates were determined on the vacuum resin transfer molding specimen both in tensile and flexural testing. The effect of carbon nanotube concentration (0.1, 0.2, 0.3%) and applied voltage of electrospray (10, 15, 20 kV) towards the deposition of carbon nanotube on the woven glass fibre surfaces were examined. The morphology of carbon nanotube dispersion between glass fibre and epoxy were studied by Scanning Electron Microscope (SEM) and tensile and flexural testing respectively. The applied voltage of the electrospray is a critical parameter in producing the uniform dispersion of the carbon nanotubes fillers on glass fibres/epoxy laminated composite without agglomeration. Several formulations of laminated composite was prepared for testing and pure woven glass fibre as control samples and using Vacuum Resin Transfer Molding (VARTM). Generally, the strength and stiffness properties of the CNTs woven glass fibre are superior than the pure woven glass fibre epoxy laminates composite. The presence of finer dispersion of carbon nanotubes formed onto the surface of woven glass fibre leads to the interfacial adhesion improvement between the laminate composite. The concentration and applied electrospray voltage were varied and the mechanical properties of specimen were compared. It was found out that the addition of MWCNT using electrospraying techniques improves the mechanical, thermal and dielectric properties of Epoxy/GF/MWCNTs laminates. Epoxy/GF/MWCNTs laminates composites exhibits improvement in the tensile strength by up to 6.7% and tensile modulus of 4.9% compared to Epoxy/GF laminates respectively. Apart from that, flexural properties are greatly improved for Epoxy/GF/MWCNTs together with improvement in thermal conductivity by 5.7% and dielectric constant by 6.20%. In conclusion, the effect of 0.2% carbon nanotube concentration with maximum electrospray voltage utilization at 20 kV is the best electrospraying formulation to use to produce the glass fibre epoxy laminated composite.